Financial Planning in a Regulated Environment - Machado, Ezequiel L.; Carleton, Willard T. (Journal of Financial and Quantitative Analysis, 1978)
Ezequiel L. Machado, Willard T. Carleton, Financial Planning in a Regulated Environment, The Journal of Financial and Quantitative Analysis, Vol. 13, No. 4, Proceedings of Thirteenth Annual Conference of the Western Finance Association, June 20-26, 1978 (Nov., 1978), pp. 759-777